2016
DOI: 10.1186/s13063-016-1619-3
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based self-help therapy with FearFighter™ versus no intervention for anxiety disorders in adults: study protocol for a randomised controlled trial

Abstract: BackgroundInternet-based self-help psychotherapy (IBT) could be an important alternative or supplement to ordinary face-to-face therapy. The findings of randomised controlled trials indicate that the effects of various IBT programmes for anxiety disorders seem better than no intervention and in some instances are equivalent to usual therapy. In Denmark, IBT is part of future treatment plans in mental health care services, but the verification level of the current clinical scientific knowledge is insufficient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…One example is the study by Kok, van Straten, Beekman and Cuijpers [36] who examined the efficacy of an Internet-based exposure intervention with weekly support for outpatients waiting for face-to-face psychotherapy for several phobias. In addition, several studies have tested the FearFighter™ program [37] for the treatment of panic and phobia disorders [3840], which is used in the mental health services in England [41]. Finally, from a transdiagnostic perspective, Schöder, Jelinek and Moritz [42] conducted a randomized controlled trial of an Internet intervention for individuals with panic and phobias.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the study by Kok, van Straten, Beekman and Cuijpers [36] who examined the efficacy of an Internet-based exposure intervention with weekly support for outpatients waiting for face-to-face psychotherapy for several phobias. In addition, several studies have tested the FearFighter™ program [37] for the treatment of panic and phobia disorders [3840], which is used in the mental health services in England [41]. Finally, from a transdiagnostic perspective, Schöder, Jelinek and Moritz [42] conducted a randomized controlled trial of an Internet intervention for individuals with panic and phobias.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a shortage of similar studies, it is not currently possible to conduct a calculation of optimal sample size for this study. Based on existing knowledge about feasibility study methodology [6,52,54] and two feasibility studies of mHealth tool in public health settings [9,26], we plan to recruit 70 patients. With 70 patients, the 95% confidence interval for a proportion estimate such as compliance would range between 0.38 and 0.62 (if the observed proportion is 0.50), which we consider acceptable for planning further studies.…”
Section: Sample Sizementioning
confidence: 99%
“…As explained above, to date, studies about the relative benefits of guided vs. unguided support in Internet delivered interventions have reached different conclusions. The literature shows that guidance is a beneficial feature resulting in better adherence and better outcomes [34,[39][40][41]. However, some studies have shown the efficacy of self-guided treatments (without any contact or support from a therapist, consultant or researcher) [43][44][45][46][47]71].…”
Section: Discussionmentioning
confidence: 99%
“…To date, evidence shows that guidance is a beneficial feature that leads to better adherence and better outcomes in programs administered through the Internet [34,[39][40][41]. Nevertheless, other authors have shown that unguided self-help interventions are useful alternatives with similar outcomes that might work using automated reinforcement [40,42,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation